AKSELERASI DAYA SAING KOPI BANGLI: INTEGRASI TRANSFORMASI DIGITAL DAN STRATEGI KOLABORASI PEMASOK - I Made Kartika; I Made Adi Suwandana; I Dewa Gede Putra Sedana; I Made Darsana (Penerbit Lafadz Jaya, 2026)
The specialty coffee industry in Bangli Regency, particularly Kintamani Arabica Coffee, is currently facing the challenges of the global market in the Fourth Wave Coffee era, which demands traceability and high efficiency. This study aims to analyze the influence of digital transformation and supplier collaboration in improving coffee supply chain capabilities in Bangli Regency, Bali Province. By integrating the Resource-Based View (RBV) and Dynamic Capabilities theories, this study positions technology and strategic partnerships as key drivers of regional competitiveness. The research method used is a quantitative explanatory survey technique with 100 business actors in the coffee supply chain in Bangli Regency. Data were collected through a structured questionnaire and analyzed using Partial Least Squares (PLS) through SmartPLS 4.0 software. The results reveal that digital transformation fundamentally improves operational visibility and agility through real-time data synchronization. In addition, supplier collaboration based on trust and knowledge sharing within the Subak Abian system has been shown to strengthen supply stability and consistent raw material quality. Digitalization also plays a crucial role in strengthening the legitimacy of Geographical Indication (GI) certification through a digital traceability system. Overall, supply chain capabilities act as a strategic mechanism that converts digital and relational resources into sustainable competitive advantage. This study recommends strengthening digital infrastructure in rural Bangli and improving technological literacy among smallholder farmers to minimize information asymmetry in the international market.